Ascertaining the Peculiarities of Athletes' Adaptation Course to Post-Sports Life - Valentina Voronova; Oksana Shynkaruk; Viktoriya Kovalchuk; Galina Marchenko (OVS LLC, 2024)
Objectives. The purpose of the study was to identify the peculiarities of athletes' adaptation to post-sport life under modern conditions of reality. Materials and methods. The study involved 36 athletes, Masters of Sports, aged 25 to 40 years, who had finished their professional sports careers in disciplines such as ballroom dancing, artistic gymnastics, football, swimming, and judo. The study used methods of analysis and generalization obtained from scientific-methodical literature and internet data, surveys, and psychodiagnostics: the "Differential Emotions Scale" by C. Izard, adapted by A. Leonova, the "Meaningful Life Orientations" method by D. A. Leontiev, an adapted version of the "Purpose-in-Life Test" (PIL) by James Crumbaugh and Leonard Maholick, as well as the "Zimbardo Time Perspective Inventory" (ZTPI) by Zimbardo, P. G., & Boyd, J. N. During the study results' analysis, the following methods were used: frequency analysis - identification of the frequency of each emotion category (absolute frequencies), and a calculation of percentage values (relative frequencies) for each category relative to the total number of participants. This was also applied to determine the number of athletes belonging to each category of future plans and to define the components of the time perspective; descriptive statistics - calculation of the mean value for each survey scale; these values were used to compare mean values between different scales and to analyze the variability of responses by calculating the standard deviation; percentage calculation. Results. This study examined the post-sport adaptation of 36 athletes using psychodiagnostic methods, thereby uncovering a complex emotional landscape and a variety of future perspectives. The survey results showed that 43% of the respondents had not yet decided what they wanted to become in their post-sports life, indicating significant stress, negative emotions, and physical and psychological problems that require attention and support. A significant portion (40%) of respondents affirmed that they could envisage their future without sports, with 25% choosing to become coaches and 15% interested in sports-related professions. Only 17% of respondents considered their future in other fields. The study also found that 42% of athletes reported having a strongly negative attitude towards leaving professional sports, experiencing feelings such as despair, grief, anger, disgust, and confusion. Another 36% of athletes characterized their emotional state as anxious-depressive, which also requires attention. Meanwhile, 22% of respondents stated a positive emotional attitude towards ending their careers, demonstrating interest in new circumstances and their future, which helps them to transition effectively into new lives. The study results on life orientations revealed that athletes tended to be more focused on past achievements and current goals than on the future, which may complicate their adaptation to post-sports life. Nevertheless, 37% of athletes are oriented towards a positive future and are willing to make efforts to achieve the necessary goals. Therefore, the findings clearly indicate the need for post-sports support and increased attention to the large proportion of former athletes (79%), whose mental health depends on the timeliness and speed of measures taken by specialists. Conclusions. The transition process for athletes after ending their professional careers to a life without sports is defined as individually nuanced, complex, and prolonged; it depends on past career success, is accompanied by stressful situations and negative emotions, and often requires a sudden conclusion to preserve the sense of being a champion.